THE USE OF MIND MAPPING STRATEGY TO IMPROVE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - Erlin Ernawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2018)
The study focuses on the use of mind mapping strategy to improve students’ ability in writing procedure text. The researcher designed an action research which consists of two cycles. The students were given some treatments and writing tests in order to obtain a description about students’ ability in writing procedure text. This study was held in SMK Negeri 1 Sampang for two months in Class XMM2 in the academic year of 2014/2015. Based on the pre eleminary research, the students’ achievement in reading, speaking and listening aspect of the procedure text as material at first semester was good. However, they still have low achievement in producing procedure text. There were fourteen students in this class and three kinds of writing test in this research. They were pre-test, and tests after cyle. Besides, observation checklist and questionnaire were given to support the primary data. The mean of the pre-test was 56.67, the mean of the writing test in second cycle was 63.214, and the mean of the post test was 87.792. By comparing the result of the three tests, it can be concluded that mind mapping method could give better achievement for the students in producing procedure text. The analysis of the questionnaire and observation also supported the fact that mind mapping method was appropriate to be implemented in teaching learning writing procedure text. Besides, Mind mapping method could be applied not only in writing procedure text, but also other texts which were taught both in senior and junior high school